Reconstruction of large oroantral defects using a pedicled buccal fat pad - Yang, Sunin (Maxillofac Plast Reconstr Surg, 2018)
BACKGROUND: Oroantral communicating defects, characterized by a connection between the maxillary sinus and the oral cavity, are often induced by tooth extraction, removal of cysts and benign tumors, and resection of malignant tumors. The surgical defect may develop into an oroantral fistula, with resultant patient discomfort and chronic maxillary sinusitis. Small defects may close spontaneously; however, large oroantral defects generally require reconstruction. These large defects can be reconstructed with skin grafts and vascularized free flaps with or without bone graft. However, such surgical techniques are complex and technically difficult. A buccal fat pad is an effective, reliable, and straightforward material for reconstruction. CASE PRESENTATION: This report describes three cases of reconstruction of large oroantral defects, all of which were covered by a pedicled buccal fat pad. Follow-up photography and radiologic imaging showed successful closure of the oroantral defects. Furthermore, there were no operative site complications, and no patient reported postsurgical discomfort. CONCLUSION: In conclusion, the use of the pedicled buccal fat pad is a reliable, safe, and successful method for the reconstruction of large oroantral defects.